E-assessment in collaborative blended learning: evolving practices and students’ perceptions - Loureiro, Maria João (2012)
This study reports on evolving practices of e-assessment in higher education collaborative blended learning contexts based on the paradigm of assessment for learning. Taking into account the results of a previous study, the paper describes the e-assessment strategies explored in two Distance Education post-graduation modules and their evolution. In the modules, students were asked to collaboratively write a literature review about a topic of their choice. The e-assessment activities included teachers as well as self and peer assessment. A qualitative approach was used to analyze the students‘ perceptions about the used online assessment strategies. The results show that the changes introduced lead to an increase in the number of students valuing the e-assessment tasks and, thus, that the success of online peer assessment seems to be dependent on the students‘ perceptions. Exploring the learners‘ voice, recommendations are put forward in order to take full advantage of online assessment for learning.